Faktor – Faktor Determinan Keputusan Nasabah Menjadi Debitur Kartu Kredit PT Bank Negara Indonesia (Persero) Tbk - Tappi, Yermia (Universitas Sam Ratulangi, 2018)
The purpose of research to be achieved is to determine what factors affect the decision of the customer to credit card debtors PT. Bank Negara Indonesia (Persero) Tbk. This research type is type of associative research by using data analysis factor analysis technique (Confirmatory Factor Analysis). Based on result of research indicate that there are 4 factors that determine customer to credit card debtors in PT. Bank BNI Tbk Manado. The first factor that determines the customer becomes credit card debtors in PT. Bank BNI Tbk Manado is a product benefit, the second factor that determines the customer to be a credit card in PT. Bank BNI Tbk Manado is the perception of service, the third factor that determines the customer to credit card debtors in PT. Bank BNI Tbk Manado is a trust in a brand and the fourth factor that determines customers to credit card debtors in PT. Bank BNI Tbk Manado is the consumer's taste.Keywords: Bank marketing, service quality, customer satisfaction, image, customer loyalty, use decisions